Carotenoids in Potato Tubers: A Bright Yellow Future Ahead - Monica Sturaro (Plants)
Carotenoids, the bright yellow, orange, and red pigments of many fruits and vegetables, are essential components of the human diet as bioactive compounds not synthesized in animals. As a staple crop potato has the potential to deliver substantial amounts of these nutraceuticals despite their lower concentration in tubers compared to edible organs of other plant species. Even small gains in tuber carotenoid levels could have a significant impact on the nutritional value of potatoes. This review will focus on the current status and future perspectives of carotenoid biofortification in potato with conventional breeding and biotechnological approaches. The high biodiversity of tuber carotenoid levels and composition is presented, with an emphasis on the under-exploited native germplasm that represents a wide reservoir of useful genetic variants to breed carotenoid-rich varieties. The following section describes the structural genes involved in carotenoid metabolism and storage known to have a major impact on carotenoid accumulation in potato, together with the strategies that harnessed their expression changes to increase tuber carotenoid content. Finally, the little information available on the regulation of carotenoid metabolism and the desirable future advances in potato carotenoid biofortification are discussed.